Real-World Scenarios With Negative Interest Rates based on the LIBOR Market Model. Issue 5 (2nd November 2018) - Lopes, Sara Dutra; Vázquez, Carlos
ABSTRACT: In this article, we present a methodology to simulate the evolution of interest rates under real-world probability measure. More precisely, using the multidimensional Shifted Lognormal LIBOR market model and a specification of the market price of risk vector process, we explain how to perform simulations of the real-world forward rates in the future, using the Euler‒Maruyama scheme with a predictor‒corrector strategy. The proposed methodology allows for the presence of negative interest rates as currently observed in the markets.